Implementation of the Congklak Traditional Game in Madrasah Ibtidaiyah and Elementary School - Yantoro, Yantoro; Kurniawan, Dwi Agus; Silvia, Ninda (Jurnal Pendidikan Agama Islam, 2021)
This study aims to find out how the response and character of the curiosity and love for the homeland of students in SD and MI with the application of the traditional game Congklak in the learning process. The research method used was a mixed method with a sequential explanatory model, with a sample of 60 students from both schools obtained by random sampling. Researchers used questionnaires to collect data and interviews as support. The data analysis used is descriptive analysis and hypothesis testing using the T-test. From the application of the traditional game of congklak, significant results are obtained that there are differences in the results of SD Negeri and MI Negeri. However, the response as well as the students' curiosity and love for the homeland from the application of the traditional game of congklak were in the good category.